2014
DOI: 10.5137/1019-5149.jtn.11612-14.1
|View full text |Cite
|
Sign up to set email alerts
|

Tophaceous gout of the lumbar spine: case report and review of the literature

Abstract: Tophaceous gout has classically been described as an affliction of the extremities. It has however been reported as early as 1947 to involve the spinal column. We report a 63-year-old male, previously scheduled for Anterior Cervical Discectomy and Fusion to correct an existing cervical myelopathy at the C3-C4 spinal level, who presented to the emergency room with progressive weakness of the lower extremities and inability to ambulate for three days. Physical examination suggested a possible worsening of his ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 11 publications
0
9
0
2
Order By: Relevance
“…В некоторых научных статьях, посвященных внутрикостным подагрическим тофусам, описывалась манифестная клиника подагры с ее лабораторным подтверждением, и отсутствовала связь образования кист с инъекциями ГКС [41,42,43,44,45,46,47,48,49]. Статей, описывающих локализацию тофусов в проксимальном отделе плечевой кости, не было обнаружено.…”
Section: Discussionunclassified
“…В некоторых научных статьях, посвященных внутрикостным подагрическим тофусам, описывалась манифестная клиника подагры с ее лабораторным подтверждением, и отсутствовала связь образования кист с инъекциями ГКС [41,42,43,44,45,46,47,48,49]. Статей, описывающих локализацию тофусов в проксимальном отделе плечевой кости, не было обнаружено.…”
Section: Discussionunclassified
“…It has been suggested that poor vascularization of spinal disc cells in patients with risk factors such as dyslipidemia, obesity, and a sedentary lifestyle, creates an environment for tophi deposition [6]. Furthermore, if a patient has degenerative joint disease of the spine it decreases oxygen and creates an acidic area with increased risk for deposition of monosodium urate crystals [6]. In fact, our patient had dyslipidemia and degenerative joint disease, both making him a candidate at risk for spinal tophi.…”
Section: Discussionmentioning
confidence: 99%
“…The exact mechanism of gouty tophi formation in the axial skeleton is not clear. Volkov et al 11 suggested that the poor vascularization within the area may be a contributing factor. The patient’s hyperlipidemic state, obese body habitus, and minimal physical activity can cause a small caliber vasculature in the axial skeleton, which can lead to inability to adequately filter the uric acid deposited in that area.…”
Section: Discussionmentioning
confidence: 99%
“…Their appearance can mimic neoplasm or abscess, or they can cause cervical neck pain and spinal instability, frequently seen in degenerative process disorders. 11 14 The most common symptom is back pain, accounting for 65.4%–68.5% of patients suffering from neurological deficits, including radiculopathy, loss of sensation, motor weakness, bowel/bladder dysfunction, and quadriparesis. 3 All segments of the spine could be affected by gout, and most of the gout tophi are located in the lumbar spine, followed by the cervical vertebrae.…”
Section: Discussionmentioning
confidence: 99%